Empire and Identity in Guizhou : Local Resistance to Qing Expansion - Weinstein, Jodi L. (Book collections on Project MUSE., 2013)
"Empire and Identity in Guizhou is a study of stormy ethnic relations in eighteenth-century Guizhou Province between the Qing state and the Zhongjia ethnic group, which culminated in the Nanlong Uprising in 1797. As the imperial state extended its control into frontier areas such as Mongolia, Tibet, and the southwest, it encountered difficulty incorporating non-Han people into the empire. The Zhongjia in particular were difficult to control, because the state could not employ religion as a political tool, as it did with ethnic minorities who were Buddhist; nor were literary tactics useful with the nonliterate Zhongjia. Weinstein shows how the Zhongjia maintained autonomy through livelihood choices, and how their "creative resistance" ranged from subterfuge to outright rebellion. This engagingly written and dramatic case study demonstrates how the Qing empire really worked and contributes toward a broader understanding of imperialism and colonialism"--